2002
DOI: 10.1074/jbc.m204866200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for the Local Conformational Rearrangement of Human Phosphoserine Phosphatase

Abstract: Human phosphoserine phosphatase (HPSP) regulates the levels of glycine and D-serine, the putative co-agonists for the glycine site of the NMDA receptor in the brain. Here, we describe the first crystal structures of the HPSP in complexes with the competitive inhibitor 2-amino-3-phosphonopropionic acid (AP3) at 2.5 Å, and the phosphate ion (Pi) and the product uncompetitive inhibitor L-serine (HPSP⅐L-Ser⅐Pi) at 2.8 Å. The complex structures reveal that the open-closed environmental change of the active site, ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 24 publications
(31 reference statements)
2
42
0
Order By: Relevance
“…The previously determined crystal structures of PSP have revealed that PSP belongs to the HAD-like hydrolase fold (30,31). As expected, the overall structure of ThrH is similar to that of PSP.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…The previously determined crystal structures of PSP have revealed that PSP belongs to the HAD-like hydrolase fold (30,31). As expected, the overall structure of ThrH is similar to that of PSP.…”
Section: Resultssupporting
confidence: 53%
“…Substrate binding-induced conformational changes that results in a "closed" active site have been a common theme in several HAD superfamily enzymes (9,31,36). The conformational differences between the two independent ThrH monomers in the asymmetric unit demonstrated the structural flexibility of ThrH especially at the hinge region between domains I and II.…”
Section: Discussionmentioning
confidence: 99%
“…9 Interpretation of the effect of the two mutations Structure analysis of Methanococcus jannaschii phosphoserine phosphatase indicates that Met43, which aligns with Met52 in the human enzyme, contacts the substrate in a closed conformation of the protein. 16 In the human structures, which are in slightly different open conformations, 17,18 Met52 and the surrounding amino acids in the sequence are disordered, presumably allowing phosphoserine to access the catalytic site and the products to leave it. It has been proposed that the extremely conserved methionine is an important factor in switching the enzyme from the open to the closed conformation by interacting with the substrate.…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes have an absolute requirement for divalent metal ion, and the conserved Asp residue in motif I forms a phosphoenzyme intermediate with the substrate via nucleophilic attack (19,20). HAD family of enzymes possess the Rossmannoid ␣/␤ fold and an inserted "cap" that regulates substrate access to its active site (21)(22)(23). PSP enzymes have been extensively biochemically characterized in various microorganisms and have been demonstrated to facilitate entry of Porphyromonas gingivalis into host cells by modulating host cytoskeletal architecture, innate immune responses, and dephosphorylating colicin and NF-〉 (24 -26).…”
Section: Tuberculosis (Tb)mentioning
confidence: 99%